PEMANFAATAN KOMPOS PADA LAHAN KRITIS UNTUK MENUNJANG PRODUKSI BAWANG MERAH, KACANG TANAH, DAN KEDELE DI KABUPATEN MINAHASA UTARA - Supit, Joice M.J.; Kamagi, Yani E.B.; Kumolontang, Wiesje J. (EUGENIA, 2016)
ABSTRACT   The  experiment  pot  of  the effect  compost in the critical  land on the  production  onions, peanuts, and soybeans, the goal is to get organic  agricultural  production and determine the optimal dose of compost for plant onions, peanuts and soybeans. Before  the experiment of compost treatment  was  conducted  the  compost and  soil  as  media plant  to analyse  the chemical  properties. After  the experiment of compost treatment  was conducted  the soil as  media  plant  to analyse the chemical properties. The  experiment  design of methode  was  used  complate  randamized design (CRD) with the  five treatment compost and four replication.   Dosage of compost consists of  0 tonnes/ha  (0 g/pot)  as a control,  30 tonnes /ha  (75 g /pot);  60 tonnes/ha (150 g/pot);  90 tonnes/ha (225 g/pot),  and 120 tonnes/ha (300  g/pot). The parameter were observed  wet  weight of  plants,  quantity and weight  beet  the production  plant of onions;  wet weight  of  plants, quantity and weight of  pod pea and  seed  the  production  plant  of  peanuts and  soyabeans.  The  data of  analysis  was  used  the  analysis  of variance (Anova)  and  the  least significant  difference (LSD). The results showed  that  treatment  of compost very significant  effect  on  the growth  and  production of plant onions, peanuts and soybeans. Treatment  compost  90 tonnes/ha (225 g/pot)  provide  growth and  yield  of  plant  onion, peanuts, and soybeans maximum. Keywords: compost, onion, peanut, soybean, critical land